2021
DOI: 10.1039/d0ra08737h
|View full text |Cite
|
Sign up to set email alerts
|

LiCl-promoted-dehydration of fructose-based carbohydrates into 5-hydroxymethylfurfural in isopropanol

Abstract: Fructose-based carbohydrates can be dehydrated into HMF in the LiCl-promoted and i-PrOH mediated system efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…The linear regression of the logarithm of the reaction rate constant ln K vs the reciprocal of temperature 1/ T was ploted according to the Arrhenius equation. The activation energy of the conversion of fructose into HMF by using the H2 catalyst was 55.8 kJ/mol (Figure S10), which was lower than other reported catalytic systems. The results further indicated that the H2 catalyst showed higher catalytic efficiency and can more effectively catalyze the conversion reaction of fructose. The effective conversion of fructose into HMF catalyzed by the carbon-based catalyst demonstrated its great application potential.…”
Section: Results and Discussionmentioning
confidence: 87%
“…The linear regression of the logarithm of the reaction rate constant ln K vs the reciprocal of temperature 1/ T was ploted according to the Arrhenius equation. The activation energy of the conversion of fructose into HMF by using the H2 catalyst was 55.8 kJ/mol (Figure S10), which was lower than other reported catalytic systems. The results further indicated that the H2 catalyst showed higher catalytic efficiency and can more effectively catalyze the conversion reaction of fructose. The effective conversion of fructose into HMF catalyzed by the carbon-based catalyst demonstrated its great application potential.…”
Section: Results and Discussionmentioning
confidence: 87%
“…In methyl-isobutyl-ketone/2-butanol at 165 °C, d -fructose was catalyzed by solid acid TiO 2 -SO 3 H within 3 h, and the conversion rate of d -fructose was 99%, while the 5-HMF yield was 50% . Using LiCl and i -PrOH as catalysts at 130 °C, 9 g of d -fructose was dehydrated to 5-HMF (73% yield) after 2 h . Using Si-3-IL-HSO 4 as a catalyst and DMSO as an extractant, the conversion rate of d -fructose into 5-HMF reached 60% (130 °C, 1 h) .…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the DES Bet:BSA was a better chemocatalyst and solvent for efficient catalysis of d -fructose to 5-HMF in a good yield after a short dehydration time (2 min) compared to choline chloride:boric acid, LiCl, ACS/ChCl-4-phenol, TiO 2 -SO 3 H, Nb 2 O 5 , Si-3-IL-HSO 4 , Lewatit K2420, CH 3 SO 3 H, and SBA-15-SO 3 H (Table ). , In addition, E. coli DCF containing a powerful reductase was constructed and employed to biologically catalyze 5-HMF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, in continuation of our work on green catalytic production of HMF, we have explored imidazolium- and pyridinium -based zwitterionic-type molten salts, viz., inner salts, as a new class of neutral organocatalysts in the dehydration of fructose-based carbohydrates into HMF. These requisite zwitterionic-type inner salts have been designed and prepared to elucidate the cooperation of the cation and anion.…”
Section: Introductionmentioning
confidence: 99%